Acoustic and perceptual effects of telephone transmission on vowel quality. - Lawrence, Sophie; Nolan, Francis; McDougall, Kirsty (International Journal of Speech, Language and the Law, 2009)
This study investigates acoustic and perceptual effects of telephone transmission on the vowels /i:/, /ae/ and /u:/ in Standard Southern British English. The aim of the study was to determine whether the ‘telephone effect’ described for vowels by Künzel (2001) has an effect on perception as well as on acoustic information. Acoustic measurements confirmed that telephone-transmitted high vowels experience a shift in the frequency of F1. Secondly, a perceptual experiment was carried out in which phoneticians were asked to plot vowels recorded directly and over the telephone on a vowel quadrilateral. Comparing the points plotted for the same tokens recorded directly and over the telephone showed no clear pattern of a perceptual effect of the telephone. However phoneticians’ responses exhibited extensive individual variation, raising a number of questions for future research about the reliability of the auditory analysis of speech. Implications for forensic speaker comparison are discussed.